Determining Curve Number and Estimating Runoff Yield In HESARAK Catchment - mohammad mahdi hoseinzadeh; sepide imeni (تحقیقات کاربردی علوم جغرافیایی)
The process of precipitation – runoff of each basin, is influenced by hydrologic, geomorphology conditions, geological formation and vegetation. There are different methods in drainage basins. One way to estimate the runoff height is Curve Number (CN) method. That reperesents the hydrological behavior of basin. data were collected for statistics of climate and then topographic map of 1: 25000 and geological map of 1: 100000 by GSI was used. Smada software for calculate the short – term rainfall at different return periods. As well as Arc GIS software for mapping Curve Number by combining maps of land use, soil hydrological groups and moisture of soil with using the table of America Soil Conservation Service (SCS). And then modeling related in the GIS mappings of runoff height of Hesarak catchment was prepared. The aim of this study, was to determine Curve Number and estimate runoff coefficient and maximum discharge runoff with SCS method in various units catchment is. The results showed, hydrologic condition and soil hydrological groups are the most important parameters to determine the CN and affect on runoff. The most potential for runoff is in downstream of basin that specified with urban land use. Also average weight of Curve Numbers those obtained for each sub catchments, Chapdareh sub catchment (S2) with 88 Cure Number and mean of runoff 28.15 mm had the highest volume of runoff, Dochenaran sub catchment (S3) with 89.3 Curve Number and mean of runoff 24.54 mm and sub catchment of the twin branches (S1) with 90.1 Curve Number and mean of runoff  17.36 mm had The lowest amount of runoff probability and spill potential. But in general potential runoff in this basin is relatively high. The maximum amount of runoff Curve Number in condition of high humidity is 99 and 78 is the lowest.